Factors associated with death or volume replacement in patients with trauma due to penetrating injuries - Travassos, Márcia Cristine Pires; Silva, Isabel Cristina Bandeira da; Lima, João Paulo Bessa de; Fonseca, Celso Martins; Sachett, Jacqueline de Almeida Gonçalves; Osis, Sibila Lilian (Rev Rene, 2016)
Objective: to evaluate the prognostic factors of volume replacement in patients with trauma due to penetrating injuries.Methods: retrospective cohort study whose data were obtained by analyzing medical records of 544 patients who were admitted to the emergency unit, victims of penetrating trauma. Results: among the victims, 282 (51.9%) suffered stab wound, 262 (48.2%) injury by firearms, 486 (89.3%) were male, 382 (70.2%) were aged between 14 and 30 years. Most who received volume greater than 2000ml, systolic blood pressure ≤90mmHg and mean arterial pressure ≤65mmHg presented more mortality, with p <0.05, p <0.002 and p <0.003, respectively. Conclusion: the limited volume replacement can help in the good prognosis of victims of penetrating trauma.